Microbiological Study of Male ’ s Urethral Discharge - AL – Obadi, Waleed I A (AL-Kindy College Medical Journal, 2007)
Objective: To evaluate male patients complaining ofurethritis clinically according to the isolated organisms.Method: A total of 100 male patients attending to ofDermatological and Venereal private clinics for the periodApril 2003 to November 2003 were included in the study.Urethral swab was obtained from each male for culture anddirect immunofluorescence examination was done.Demographic data was obtained, also.Results: N. gonorrhoea was the predominate cause ofinfection in 22%. A peak of infection was reported in thesecond decade of age. Highest rate reported among singlemales. A significant association was noticed betweenprofuse discharge and infection with gonorrhoea.Conclusion: This study demonstrated that peak ofinfection in the second decade of age and among singles. Abroad range of causative agents was reported.